The Lawfulness of Citizenship Deprivation: Comparing Australia and the UK - Guy Baldwin (Laws)
The rise in international terrorism has led to a rise in citizenship deprivation. Depriving a person of citizenship represents a harsh national security measure. Although both Australia and the UK have citizenship deprivation legislation, the judicial response has differed. In Australia, two laws providing for deprivation of citizenship have been found unconstitutional. In the UK, significant challenges to citizenship deprivation decisions have failed, including those relating to Shamima Begum, deprived of UK citizenship in 2019, whose request for permission to appeal in respect of the decision was rejected by the UK Supreme Court in August 2024. In this context, it is striking that despite the lesser degree of human rights protection under the Australian Constitution and federal statutes compared with the UK, the Australian courts may have arrived at a significantly rights protective approach to citizenship deprivation, leading to an important procedural safeguard by requiring courts to make decisions on citizenship deprivation. This underlines interesting features of the Australian system, in which the development of doctrines under a written constitution that limits legislative power, such as through the separation of powers, can sometimes lead to significant (if uneven) rights protective outcomes. Short of a shift in UK constitutional law doctrine around the separation of powers (which is unlikely), the Australian decisions cannot be mirrored in the UK. However, they may point towards the possibility of stronger procedural safeguards in the context of citizenship deprivation, as well as some potential human rights law implications.